Genomics‐based re‐examination of the taxonomy and phylogeny of human and simian Mastadenoviruses: an evolving whole genomes approach, revealing putative zoonosis, anthroponosis, and amphizoonosis. (14th July 2020) - Kang, June; Ismail, Ashrafali Mohamed; Dehghan, Shoaleh; Rajaiya, Jaya; Allard, Marc W.; Lim, Haw Chuan; Dyer, David W.; Chodosh, James; Seto, Donald
Abstract: With the advent of high‐resolution and cost‐effective genomics and bioinformatics tools and methods contributing to a large database of both human (HAdV) and simian (SAdV) adenoviruses, a genomics‐based re‐evaluation of their taxonomy is warranted. Interest in these particular adenoviruses is growing in part due to the applications of both in gene transfer protocols, including gene therapy and vaccines, as well in oncolytic protocols. In particular, the re‐evaluation of SAdVs as appropriate vectors in humans is important as zoonosis precludes the assumption that human immune system may be naïve to these vectors. Additionally, as important pathogens, adenoviruses are a model organism system for understanding viral pathogen emergence through zoonosis and anthroponosis, particularly among the primate species, along with recombination, host adaptation, and selection, as evidenced by one long‐standing human respiratory pathogen HAdV‐4 and a recent re‐evaluation of another, HAdV‐76. The latter reflects the insights on amphizoonosis, defined as infections in both directions among host species including "other than human", that are possible with the growing database of nonhuman adenovirus genomes. HAdV‐76 is a recombinant that has been isolated from human, chimpanzee, and bonobo hosts. On‐going and potential impacts of adenoviruses on public health and translational medicine drive this evaluation of 174 whole genome sequences from HAdVs and SAdVs archived in GenBank. The conclusion is that rather than separate HAdV and SAdV phylogenetic lineages, a single, intertwined tree is observed with all HAdVs and SAdVs forming mixed clades. Therefore, a single designation of "primate adenovirus" (PrAdV) superseding either HAdV and SAdV is proposed, or alternatively, keeping HAdV for human adenovirus but expanding the SAdV nomenclature officially to include host species identification as in ChAdV for chimpanzee adenovirus, GoAdV for gorilla adenovirus, BoAdV for bonobo adenovirus, and ad libitum .